Effect of Culture Media on In-vitro Regeneration of Anthurium (Anthurium andraeanum Lind.) from Axillary Bud Explants - Maitra, S.; Ghosh, P. D.; Roychowdhury, N.; Satya, P. (International Journal of Bio-resource and Stress Management, 2023)
Direct regeneration of anthurium from adventitious bud explant was studied. Half- MS medium, supplemented with coconut water 15% (v/v), NAA (1 mg l-1) and BAP (3 mg l-1) was found the most effective medium regarding percentage of explant survivability (84.45%), earliness in shoot production, and number of shoot and leaf production culture-1 at the time of first transfer. The other media with less cytokinin also showed effects that were less favorable as compared to this medium. Explants on growing media having MS+NAA (0-1 mg l-1)+BAP (0-3 mg l-1) and 1/2 MS+coconut water (15% v/v)+NAA (1 mg l-1)+BAP (0-1 mg l-1) failed to survive and proliferate. Results revealed that increase in the concentration of BAP pronounced the effect of the medium. ½ MS medium supplemented with coconut water 15% (v/v), NAA (1 mg l-1) and BAP (3 mg l-1) was effective for shoot regeneration of anthurium from adventitious bud explants. For early rooting ½ msmedium supplemented with NAA (1 mg l-1) and IBA (2mg l-1) was found ideal. This medium (AR2) started rooting on 39.10 days after culture. Though culture on ½ msmedium supplemented with NAA (1mg l-1)+IBA (3 mg l-1) started rooting 42.67 days after transfer but this medium (AR3) represented 84% explant survivability hence, may be advocated for rooting of anthurium micro-cuttings.